1997
DOI: 10.1007/bf02407458
|View full text |Cite
|
Sign up to set email alerts
|

Global mercury pollution and the role of gold mining: An overview

Abstract: Abstract. As described by Jernelov and Ramel (1995), the Scientific Committee on Problems of the Environment (SCOPE) sponsored an investigation of Hg in ecosystems with special emphasis on tropical regions. In these regions small-scale gold mining activities have occupied about 10 million people worldwide who use Hg for extracting gold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Mercury's complex chemical behaviour makes it one of the most problematic metals to probe using conventional geochemical tools. The anthropogenic contribution to the global atmospheric Hg budget is now well constrained (Mason et al 1994;Khalil and Rasmussen 1994;Pirrone et al 1996, Pirrone andMason 2009;Porcella et al 1997;Hylander and Meili 2003;Pacyna et al 2006;Wilson et al 2006), with most recent estimates ranging from 1484 (AMAP/UNEP 2008) to 1894 tyr -1 /2006Streets et al 2009). Hg emissions from natural sources are, on the other hand, still poorly characterised, though being likely in the same range (estimates from 500 to 3000 tyr -1 ; Nriagu 1989;Lindqvist et al 1991;Mason et al 1994;Selin et al 2007) of those reported for anthropogenic release.…”
Section: Introductionmentioning
confidence: 91%
“…Mercury's complex chemical behaviour makes it one of the most problematic metals to probe using conventional geochemical tools. The anthropogenic contribution to the global atmospheric Hg budget is now well constrained (Mason et al 1994;Khalil and Rasmussen 1994;Pirrone et al 1996, Pirrone andMason 2009;Porcella et al 1997;Hylander and Meili 2003;Pacyna et al 2006;Wilson et al 2006), with most recent estimates ranging from 1484 (AMAP/UNEP 2008) to 1894 tyr -1 /2006Streets et al 2009). Hg emissions from natural sources are, on the other hand, still poorly characterised, though being likely in the same range (estimates from 500 to 3000 tyr -1 ; Nriagu 1989;Lindqvist et al 1991;Mason et al 1994;Selin et al 2007) of those reported for anthropogenic release.…”
Section: Introductionmentioning
confidence: 91%
“…In modern Brazil, where there has been a gold rush since 1980, at least 2000 t mercury was released, with subsequent mercury contamination of sediments, soils, air, fish, and human tissues; a similar situation exists in Columbia, Venezuela, Peru, and Bolivia (Malm 1998). Recent estimates of global anthropogenic total mercury emissions range from 2000 to 4000 t/yr, of which 460 t is from small-scale gold mining (Porcella et al 1995(Porcella et al , 1997. Major contributors of mercury to the environment from recent gold mining activities include Brazil (3000 t since 1979), China (596 t since 1938), Venezuela (360 t since 1989), Bolivia (300 t since 1979), the Philippines (260 t since 1986), Columbia (248 t since 1987), the United States (150 t since 1969), and Indonesia (120 t since 1988; Lacerda 1997a).…”
Section: History Of Mercury In Gold Miningmentioning
confidence: 94%
“…While the U.S. electric utility industry uses three major fossil fuels, normally coal, fuel oil and natural gas, 35 % of the global atmospheric emission of mercury occurs from coal combustion. (24) Chu and Porcella have estimated that 89 ton/year of mercury is emitted to the atmosphere from U.S. coal-fired power plants (CFPPs) in 1990. (25) U.S EPA estimated that about 300 ton/year of mercury was emitted from anthropogenic sources in the U.S. in 1990, with 30 % of total mercury emissions coming from coal fired power plants (CFPPs).…”
Section: Mercury Emission and Control Technologiesmentioning
confidence: 99%